Generation of Loa loa infective larvae by experimental infection of the vector, Chrysops silacea. - Lontum B Ndzeshang; Fanny F Fombad; Abdel J Njouendou; Valerine C Chunda; Narcisse V T Gandjui; Desmond N Akumtoh; Patrick W N Chounna; Andrew Steven; Nicolas P Pionnier; Laura E Layland; Manuel Ritter; Achim Hoerauf; et al. (Public Library of Science (PLoS), 2020)
Basic and translational research on loiasis, a filarial nematode infection of medical importance, is impeded by a lack of suitable Loa loa infection models and techniques of obtaining and culturing life cycle stages. We describe the development of a new method for routine production of infective third-stage larvae (L3) of L. loa from the natural intermediate arthropod vector host, Chrysops silacea, following experimental infection with purified microfilariae. At 14-days post-infection of C. silacea, the fly survival rate was 43%. Survival was significantly higher in flies injected with 50 mf (55.2%) than those that received 100 mf (31.0%). However, yield per surviving fly and total yield of L3 was markedly higher in the group of flies inoculated with 100 mf (3474 vs 2462 L3 produced). The abdominal segment hosted the highest percentage recovery of L3 (47.7%) followed by head (34.5%) and thorax (17.9%). L. loa larval survival was higher than 90% after 30 days of in vitro culture. The in vitro moulting success rate to the L4 larval stage was 59.1%. After experimental infection of RAG2-/-IL-2γc-/-mice, the average L. loa juvenile adult worm recovery rate was 10.5% at 62 dpi. More than 87% of the worms were recovered from the muscles and subcutaneous tissues. Worms recovered measured an average 24.3 mm and 11.4 mm in length for females (n = 5) and males (n = 5), respectively. In conclusion, L. loa mf injected into C. silacea intrathoracically develop into infective larvae that remain viable and infective comparable to L3 obtained through natural feeding on the human host. This technique further advances the development of a full laboratory life cycle of L. loa where mf derived from experimentally-infected animals may be utilized to passage life cycle generations via intrathoracic injections of wild-caught vector hosts.